2020
DOI: 10.1017/s1431927620024538
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Distribution of E-Cadherin, p63, and Mitotic Figures in ApoTome Images to Determine the Oncogenic Potentiality of Oral Submucous Fibrosis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Since the TEM data showed that the vesicles in FN mutants are covered by ribosomes and appear to be arising from the RER, we next tested a series of ER and intracellular vesicle and organelle markers in the MSCs using super resolution structured illumination microscopy (23, 24)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the TEM data showed that the vesicles in FN mutants are covered by ribosomes and appear to be arising from the RER, we next tested a series of ER and intracellular vesicle and organelle markers in the MSCs using super resolution structured illumination microscopy (23, 24)…”
Section: Resultsmentioning
confidence: 99%
“…Since the TEM data showed that the vesicles in FN mutants are covered by ribosomes and appear to be arising from the RER, we next tested a series of ER and intracellular vesicle and organelle markers in the MSCs using super resolution structured illumination microscopy (23,24) We first analyzed the abundant ER chaperone BIP/GRP78, a member of the heat shock protein 70 family, which assists in protein folding and mediates retention of misfolded proteins (25,26). In the control MSCs we observed a punctate BIP staining throughout the cell cytoplasm (Figure 5A).…”
Section: Misfolded Mutant Fn Is Exported Directly From Rough Endoplas...mentioning
confidence: 99%